Disease-associated gut microbiome and metabolome changes in patients with chronic obstructive pulmonary disease - Kate L. Bowerman (Nature Portfolio, 2020)
Chronic obstructive pulmonary disease (COPD) is a progressing disease, with lung but not gut microbiota implicated in its etiology. Here the authors compare the stool from patients with COPD and healthy controls to find specific gut bacteria and metabolites associated with active disease, thereby hinting at a potential role for the gut microbiome in COPD.